Medicinal plants use as an anti-inflammatory agent: a brief review on molecular pharmacological approach - Kishor Kumar Roy; Dibyendu Shil; Rasamalla Mounika; Md Masud Reja; Subhasish Saha; Ranjan Kumar Maji (Creative Pharma Assent, 2022)
Inflammation is a vital therapeutic target for creating new methods for pharmacological interventions, aside from being a stage in the pathophysiology of many diseases, such as atherosclerosis and rheumatoid arthritis. Thus, molecular understanding of inflammation has led to new opportunities for drug creation and significant new implications for current clinical medicine. It has also revealed the biological targets and mechanisms of therapeutic action, opening up new opportunities to alter complex biological systems. Meanwhile, using medicinal plants to control inflammation has been recommended as an alternative to traditional therapeutic approaches for a variety of conditions, particularly when suppression of inflammation is anticipated. Several medicinal plant species have been demonstrated to have strong anti-inflammatory properties in contemporary research. The review article was discussed about the chemical constituents and biological properties of therapeutically active plants including curcumin from Curcuma longa and epigallocatechin-3-gallate from Camellia sinensis, including the molecular pharmacology of active constituents against inflammation.